Multiparametric Magnetic Resonance Investigation of Brain Adaptations to 6 Days at 4350 m - Verges, Samuel; Rupp, Thomas; Villien, Marjorie; Lamalle, Laurent; Troprés, Irène; Poquet, Camille; Warnking, Jan M.; Estève, François; Bouzat, Pierre; Krainik, Alexandre (Frontiers in Physiology, 2016)
Objective. Hypoxic exposure in healthy subjects can induce acute mountain sickness including headache, lethargy, cerebral dysfunction and substantial cerebral structural alterations which, in worst case, can lead to potentially fatal high altitude cerebral edema. Within this context, the relationships between high altitude-induced cerebral edema, changes in cerebral perfusion, increased brain parenchyma volume, increased intracranial pressure and symptoms remain unclear. Methods. In 11 subjects before and after 6 days at 4,350 m, we performed multiparametric magnetic resonance investigations including anatomical, apparent diffusion coefficient and arterial spin labelling sequences. Results. After the altitude stay, while subjects were asymptomatic, white matter volume (+0.7±0.4%, p=0.005), diffusion (+1.7±1.4%, p=0.002) and cerebral blood flow (+28±38%; p=0.036) were significantly increased while cerebrospinal fluid volume was reduced (-1.4±1.1%, p=0.009). Optic nerve sheath diameter (used as an index of increased intracranial pressure) was unchanged from before (5.84±0.53 mm) to after (5.92±0.60 mm, p=0.390) altitude exposure. Correlations were observed between increases in white matter volume and diffusion (rho=0.81, p=0.016) and between changes in cerebrospinal fluid volume and changes in optic nerve sheath diameters (rho=-0.92, p=0.006) and symptoms during the altitude stay (rho=-0.67, p=0.031). Conclusions. These data demonstrate white matter alterations after several days at high altitude when subjects are asymptomatic that may represent the normal brain response to prolonged high altitude exposure.